Ultrasonic-assisted extraction of essential oil from Botryophora geniculate using different extracting solvents - Habibullah, (American Institute of Physics Inc., 2016)
This study compares the performance of ionic liquids to substitute conventional solvents (hexane, dichloromethane and methanol) to extract essential oil from Botryophora geniculate plant. Two different Ionic liquids (C3MIMAc, C4MIMAc) with co-solvent diethyl ether were used in the ultrasonic-assisted extraction. The effect of various experimental conditions such as time, temperature and solvent were studied. Gas chromatography-mass spectroscopy (GC-MS) was used to analyze essential oils. The results showed that in ultrasonic-assisted extraction using ionic liquids as a solvent gave highest yield (9.5%) in 30 min at temperature 70°C. When using ultrasonic bath with hexane, dichloromethane and methanol, yields was (3.34%), (3.6%) and (3.81%) at 90 min, respectively were obtained. The ultrasonic-assisted extraction under optimal extraction conditions (time 30 min, temperature of 70°C) gave the best yield for the essential oil extraction. © 2016 Author(s).